Complete treatment of a patient with bruxism - Krisztina Török (Hungarian Dental Association, 2022)
Bruxism is a condition of multifactorial origin, defined differently in different textbooks. According to one of the definitions it is either a daytime or night-time parafunction that includes clenching and grinding. Bruxism can occur while sleeping or being awake, and these two forms can often be associated with each other. The central etiological factors include short waking cycles during sleep, a shift in the production of neurotransmitters in the central nervous system, stress and anxiety as psychosocial factors, while occlusal and anatomical abnormalities are cited as influencing factors. Clinical symptoms include heavy dental attrition, abrasion, abfraction, soft tissue lesions (linea alba, lacerated lingual edges), frictional keratosis or masticatory muscle hypertrophy, and myalgia. The aim of our case report is to present a treatment pathway for a patient with bruxism who required rehabilitation of his entire upper and lower teeth following clinical examination. The patient had missing lower right premolar and molar teeth and had a high degree of dental attrition on his lower in cisors and lower left premolars. The maxillary teeth had a complete circular bridgework (damaged on it's anterior region) and severe gingivitis due to inadequate marginal adaptation of the restoration. Based on the clinical examination and after recording the patient's status, our treatment plan was to fabricate a bridge on the remaining teeth in the anterior and left distal region and a bridge on the implants in the right distal region of the mandible. While working on the lower restorations we planned to replace the original maxillary prosthesis with a temporary one. After the lower dentition will have been restored, a full metal-ceramic circular bridge will be made to rehabilitate the upper teeth. To avoid the development of possible jaw-joint problems, we use our basic knowledge of gnathology to adjust the optimal position of the jaw by recording the individual movement paths with a facebow, intraoral drawing device and positional bites. The patient's severe abnormalities of tooth wear due to sleep bruxism have been corrected and gingivitis was also treated. During the whole course of treatment the unilateral overload and improper edge closure of the original dental prosthesis were corrected with a newly made upper circular bridge. Two mandibular bridgeworks on the remaining teeth in the anterior and distal left regions and on dental implants in the distal right region were also fabricated. The patient is satisfied with the final result of the rehabilitation, wears the nightly plastic protection splint and attends regular check-ups.